ISSUES IMPACTING THE DECISION OF YOUNG GENERATION TO USE QUICK RESPONSE CODE INDONESIA STANDARD (QRIS): EVIDENCE FROM BOGOR, INDONESIA - Ella Wandania; Mohammad Bintang Pamuncak (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
This study is aimed at finding out whether there is an impact of knowledge, services and facilities to the decision to use QRIS of University students in Bogor. This study uses a quantitative approach. The purposive sampling technique is employed. The respondents of this study are students of Tazkia Islamic University College, Pakuan University, Juanda University, and Bogor Agricultural University. To analize the data, multiple linear regression is employed. It is found that knowledge has a positive and significant effect on decisions to use QRIS however service does not affect the decision to use QRIS. Furthermore, facilities are found to have a positive and significant effect on decision to use QRIS. Simultaneously, knowledge, services and facilities affect quite strongly to the decision to use QRIS.